Acesso à informação: uma análise da lei de acesso à informação e a lei de arquivo e suas aplicações na Universidade Federal do Pará - COSTA, Rafaela Katarine Guimarães (2017)
The research seeks to understand the access to information through the Archive Law and the Law on Access to Information (LAI), at the Federal University of Pará (UFPA), Since the information in this institution is produced daily and based on normative procedures. The Archive Law nº 8.159 / 1991 says that it is the function of the Public Power to, documentary management as element of proof and information. Therefore, it emphasizes that the general provisions present in LAI in public institutions are under the rule of law as a guarantee of access to information. These institutions are responsible for ensure that the access to information, through the media for publicity as a general obligation and secrecy as an exception, stimulating the development of a culture of transparency (active and passive) and social control of public administration. The purpose of this study is to address the applicability of LAI in UFPA, mainly the access to public information, if it is complying with the normative precepts of articles 8 and 9, ensuring the transparent management and protection of information and the rights of information contained in Records or documents, produced, accumulated, and collected or not collected by the UFPA Archive System, that these documents receive adequate management since their creation, processing and collection, this process characterizes the importance of the File System in the process of access to information. Based on the analysis in the laws, the creation of archiving systems and information services that includes the Citizen Information Service (SIC) and the Integrated System of Patrimony, Administration and Contract (SIPAC) of the Federal University of Pará, Respectively in the context of Laws 12,527 / 2011 and 8,159 / 1991.